2020
DOI: 10.19055/ams.2020.11/30/1
|View full text |Cite
|
Sign up to set email alerts
|

Coping Strategies of Elite Hungarian Junior Handball Players

Abstract: Jelen tanulmányunkban magyar utánpótlás korú (14-19 éves) kézilabdázók (n=288) sportolói megküzdési stratégiáit vizsgáltuk a nemek, életkorok és a kézilabda posztok tekintetében, AthleticCopingSkillsInventory (ACSI-28) segítségével. A Csapásokkal való megküzdés (11,69 vs. 11,00; F=2,670 p<0,01) és a Szorongásmentesség (9,94 vs. 9,12; F=2,670 p<0,01) skálákon a férfiak értek el szignifikánsan magasabb átlagot. Ezzel szemben a nők magasabb átlagot mutattak a Célkitűzés/mentális felkészültség (12,12 vs. 11,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 6 publications
2
4
1
Order By: Relevance
“…Wings, both in male and female samples of handball players, show slightly lower mental skills. Compared to previous research that found that players in these positions score higher on self-confidence and achievement motivation ( Ökrös et al, 2020 ), the Serbian sample of wings players achieved high scores on anxiety, moderate self-confidence, and the lowest abilities of relaxation and imagination compared to other positions. It can be seen that players in the wing position would benefit most from working on mental skills, as well as players in the center back position in the form of the development of strategies to reduce competitive anxiety.…”
Section: Discussioncontrasting
confidence: 92%
See 4 more Smart Citations
“…Wings, both in male and female samples of handball players, show slightly lower mental skills. Compared to previous research that found that players in these positions score higher on self-confidence and achievement motivation ( Ökrös et al, 2020 ), the Serbian sample of wings players achieved high scores on anxiety, moderate self-confidence, and the lowest abilities of relaxation and imagination compared to other positions. It can be seen that players in the wing position would benefit most from working on mental skills, as well as players in the center back position in the form of the development of strategies to reduce competitive anxiety.…”
Section: Discussioncontrasting
confidence: 92%
“…Regarding gender differences in the mental skills of handball players, the obtained results indicate that female handball players show a lower degree of anxiety regulation ability than 10.3389/fpsyg.2022.960201 male handball players but, on the other hand, show a higher degree of relaxation ability. The obtained results are in line with previous research, which found that female handball players have a somewhat lower ability to regulate emotions and less coping strategies compared to male handball players (Kristjánsdóttir et al, 2018;Ivaskevych et al, 2019;Ökrös et al, 2020). Although the results on gender differences in mental skills are inconsistent, what can be noticed is those female handball players have a higher degree of emotional arousal, which does not have to be a consequence of personality traits, but the situation itself, and that aspects of competitive anxiety and performance concerns are more present with them than with male handball players.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations